2020
DOI: 10.1073/pnas.2014166117
|View full text |Cite
|
Sign up to set email alerts
|

Annually resolved Atlantic sea surface temperature variability over the past 2,900 y

Abstract: Global warming due to anthropogenic factors can be amplified or dampened by natural climate oscillations, especially those involving sea surface temperatures (SSTs) in the North Atlantic which vary on a multidecadal scale (Atlantic multidecadal variability, AMV). Because the instrumental record of AMV is short, long-term behavior of AMV is unknown, but climatic teleconnections to regions beyond the North Atlantic offer the prospect of reconstructing AMV from high-resolution records elsewhere. Annually resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 64 publications
6
48
0
Order By: Relevance
“… 44 . d Atlantic multidecadal variability (AMV) as reconstructed from a lake record from Ellesmere Island 39 . RWP Roman Warm Period, DA Dark Ages Cold Period, MCA Medieval Climate Anomaly, LIA Little Ice Age, MoW Modern Warming.…”
Section: Resultsmentioning
confidence: 99%
“… 44 . d Atlantic multidecadal variability (AMV) as reconstructed from a lake record from Ellesmere Island 39 . RWP Roman Warm Period, DA Dark Ages Cold Period, MCA Medieval Climate Anomaly, LIA Little Ice Age, MoW Modern Warming.…”
Section: Resultsmentioning
confidence: 99%
“…= dry sediments) using the calibration method described in Zander et al (2021a). TChl is used as a proxy for total algal productivity (Rein and Sirocko, 2002;Leavitt and Hodgson, 2002), whereas Bphe is produced by anoxygenic phototrophic purple sulfur bacteria and is a specific biomarker for anoxic conditions overlapping with the photic zone (Butz et al, 2015;Sinninghe Damsté and Schouten, 2006). An additional spectral index, Rmean (mean reflectance/total brightness), was used as a proxy for calcite (Butz et al, 2017) to improve the alignment of HSI and µXRF data.…”
Section: Geochemical Scanning Measurementsmentioning
confidence: 99%
“…Median values of TChl are low in Vty-3 years, though there are some years with large TChl peaks (algal blooms). Oxygenation of the water column may have limited TChl preservation (Leavitt and Hodgson, 2002).…”
Section: Classification Of Varve Typementioning
confidence: 99%
“…Numerous studies have identified close relationships between instrumental meteorological records and data obtained from varved sediments, in some cases at annual resolution, demonstrating the great potential of varves for high-resolution paleoclimatic reconstructions. The majority of these studies have related meteorological parameters with sedimentary variables in clastic varves that reflect transport of minerogenic material (Lapointe et al, 2020;Francus et al, 2002;Trachsel et al, 2010;Elbert et al, 2012). Interpretation of climate signals recorded in the sedimentary properties of biochemical and biogenic varves has proven much more challenging than in clastic varves due to more complex and often non-linear interactions between climate forcing, ecological and hydrochemical response, endogenic organic matter and mineral formation, and sedimentation (Zolitschka et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, high-resolution sediment scanning techniques, such as X-ray fluorescence (XRF) and reflectance spectroscopy have been increasingly used for environmental reconstructions, including quantitative sub-decadal climate reconstructions from varved (Amann et al, 2014;Trachsel et al, 2010;Lapointe et al, 2020) and non-varved lacustrine sediments (von Gunten et al, 2012;Boldt et al, 2015). The speed and resolution of these non-destructive scanning measurements (often 0.2-2 mm resolution) is impossible to achieve with conventional biogeochemical methods that require destructive sampling of sediment cores.…”
Section: Introductionmentioning
confidence: 99%